Partisipasi dalam Sharing Economy Melalui Pendekatan Komunikasi - Luhtfiana Prima; A. A. Ngurah Anom Kumbara; I Wayan Suwena (Department of Anthropology Udayana University, 2021)
In the mid 20th century, tourism has been reached by technology, especially with the internet network. One of the changes that is the result of technology evolution is the developing model of production and consumption of goods and services, called the sharing economy. One of the successful example of sharing economy technology that is currently popular with tourists is Airbnb. The specific objective of this research is to understand and describe thoroughly the sharing economy and its implications for cross-cultural communication of hosts and guests in in North Kuta District. Rhenald Kasali, Professor of FE UI said that